Answer:
[tex]=15.4z-12[/tex]
Explanation:
The initial expression that we have in this problem is
[tex]7.4z-5(-1.6z+2.4)[/tex]
First of all, we multiply the -5 by all the terms in the brackets. Doing so, we get the following expression:
[tex]7.4z-5(-1.6z)-5(2.4)=7.4z+8z-12[/tex]
Now we can combine the like terms, which are the terms having the same variable.
Here the like terms are:
[tex]7.4z, 8z[/tex]
and
-12
Combining the first 2 terms we get
[tex]7.4z+8z=15.4 z[/tex]
Therefore, the final expression overall is:
[tex]=15.4z-12[/tex]